2005
DOI: 10.1093/nar/gki782
|View full text |Cite
|
Sign up to set email alerts
|

Not so crystal clear: the structure of the human telomere G-quadruplex in solution differs from that present in a crystal

Abstract: The structure of human telomere DNA is of intense interest because of its role in the biology of both cancer and aging. The sequence [5′-AGGG(TTAGGG)3] has been used as a model for telomere DNA in both NMR and X-ray crystallographic studies, the results of which show dramatically different structures. In Na+ solution, NMR revealed an antiparallel G-quadruplex structure that featured both diagonal and lateral TTA loops. Crystallographic studies in the presence of K+ revealed a flattened, propeller-shaped struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
327
3
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 332 publications
(356 citation statements)
references
References 58 publications
23
327
3
3
Order By: Relevance
“…Actually, a calculation on the hybrid-1 structure [50] gave a sedimentation coefficient (S) value of 2.09 with two K + ions bound, which is in good agreement (1.5% difference) with the experimentally observed value of 2.11 (unpublished data from Prof. John Trent at the University of Louisville). It was also shown in the same report that the addition of PEG200, which may mimic the crystal condition, can shift the conformation of wtTel22 to a parallelstranded structure [38]. A more recent study has elaborated on this observation, that the presence of a high concentration PEG200 as a crowding agent can completely shift the conformation of wtTel21 ( Figure 3A) to the parallel-stranded structure [68].…”
Section: Review Of Multiple Biophysical Studiesmentioning
confidence: 60%
See 3 more Smart Citations
“…Actually, a calculation on the hybrid-1 structure [50] gave a sedimentation coefficient (S) value of 2.09 with two K + ions bound, which is in good agreement (1.5% difference) with the experimentally observed value of 2.11 (unpublished data from Prof. John Trent at the University of Louisville). It was also shown in the same report that the addition of PEG200, which may mimic the crystal condition, can shift the conformation of wtTel22 to a parallelstranded structure [38]. A more recent study has elaborated on this observation, that the presence of a high concentration PEG200 as a crowding agent can completely shift the conformation of wtTel21 ( Figure 3A) to the parallel-stranded structure [68].…”
Section: Review Of Multiple Biophysical Studiesmentioning
confidence: 60%
“…A large number of biophysical and crosslinking studies have been reported on the K + -structure of human telomeric G-quadruplexes [32][33][34][36][37][38][39][40]. Structure polymorphism of the human telomeric G-quadruplexes, particularly for the 22-nt wtTel22 sequence, has been reported by various methods.…”
Section: Review Of Multiple Biophysical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Melting curves of the antiparallel G-quadruplexes were obtained by recording the CD intensity at 292 nm. The heating rate was 1.0 °C min CD measurement has been extensively applied to study secondary structures of DNA [11][12][13]. The CD spectral features allow the approximate, but convenient, recognition of different DNA motifs.…”
mentioning
confidence: 99%